1995
DOI: 10.1021/j100031a001
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry in Ultrahigh Vacuum: Intercalation of Lithium into the Basal Plane of Highly Oriented Pyrolytic Graphite from a Poly(ethylene oxide)/LiClO4 Solid Polymer Electrolyte

Abstract: The electrochemical insertion of lithium into the basal plane of highly ordered pyrolytic graphite (HOPG-(bp)) from a LiClOdPEO solid polymer electrolyte has been examined in ultrahigh vacuum (UHV) using a carefully designed electrochemical cell. On the basis of a comparison of the data obtained with those recorded for the same interfacial system in an inert gas at atmospheric pressure, it has been concluded that the electrochemical behavior observed in UHV is indeed characteristic of the Li/L,iClO4(PEO)/HOPG(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Instrumentation.-Electrochemical measurements were conducted in a UHV chamber equipped with a Varian single-pass cylindrical mirror analyzer for Auger electron spectroscopy (AES) described in detail in Ref. 5, and also in a separate UHV chamber fitted with a Vacuum Science Workshop (VSW) hemispherical energy analyzer. 7 Nonelectrochemical Li vapor deposition experiments were performed exclusively in this latter system.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Instrumentation.-Electrochemical measurements were conducted in a UHV chamber equipped with a Varian single-pass cylindrical mirror analyzer for Auger electron spectroscopy (AES) described in detail in Ref. 5, and also in a separate UHV chamber fitted with a Vacuum Science Workshop (VSW) hemispherical energy analyzer. 7 Nonelectrochemical Li vapor deposition experiments were performed exclusively in this latter system.…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical experiments.-The procedures employed for the purification of polyethylene oxide (PEO), which involve long-term dialysis, and the casting of LiClO 4 (PEO) films, have been described elsewhere. 5,10 These films were pre-electrolyzed in situ, 6 i.e., in the same chamber where the electrochemical measurements were performed under UHV, by pressing the Li/LiClO 4 (PEO) counter reference electrode assembly against a Ni foil attached to the other sample stage. After raising the temperature to ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experiments performed in our laboratories have shown that a variety of poly(ethylene oxide) (PEO) electrolyte salt solutions display remarkably low vapor pressure, even in ultrahigh vacuum (UHV), 3 opening new prospects for investigating various aspects of UPD of highly reactive metals, such as lithium and sodium, under conditions which virtually eliminate problems associated with impurities both on the electrode surface and in the solution. Implementation of this novel strategy has already yielded interesting information regarding the UPD of Li on Au 4 and Ni 5 and the mechanism of Li nucleation on foreign substrates, 3,5 allowing in some cases comparisons to be made with the behavior of Li adsorbed by vapor deposition techniques on the same metal surfaces in UHV. 6 This paper examines the UPD of lithium on Al foil and on Al thin films vapor deposited on electronically conductive boron-doped diamond (BDD) substrates.…”
Section: Introductionmentioning
confidence: 99%